RELATIONSHIP BETWEEN BREAKFAST HABITS AND NUTRITIONAL STATUS OF SCHOOL-AGE CHILDREN - Priyantini, Diah; Ananditha, Aries Chandra; Wulandari, Yuanita; Azahra, Yasmin (Universitas Airlangga, 2025)
Introduction: The nutritional status of school-age children is still a problem and a global concern, the incidence of malnutrition in the world reaches 149.2 million children. One of the influencing factors is breakfast habits. The importance of a healthy breakfast can meet 15-30% of the recommended daily nutritional needs. This study aims to analyze the relationship between breakfast habits and the nutritional status of school-age children. Methods: This type of research is a correlational analytical study with a cross-sectional approach. A total of 90 elementary school students were recruited by total sampling. Data collection was carried out using a breakfast habit questionnaire filled out by respondents and nutritional status was determined based on body weight and height measurements. Data analysis was carried out to determine the frequency distribution and percentage of each variable studied. The statistical analysis used was the Spearman rho test (p value <0.5). Results: The results showed that most students had poor breakfast habits (66.7%) and poor nutritional status (60%). The results of the relationship test showed that there was a relationship between breakfast habits and nutritional status (p = 0.000). Conclusion: Breakfast habits related to the nutritional status of elementary school students, it is expected that parents can improve their parenting patterns and knowledge of the importance of breakfast for children properly and balanced nutritional intake so that nutritional status is in the good category.